Glucose-6-phosphate dehydrogenase deficiency screening and gene analysis in blood donors of Guangdong province. Issue 1 (31st December 2022) - Liang, Hong-Feng; Lin, Fen; Lu, Jin; Chen, Zhi-Xiao; Yang, Li-Ye
ABSTRACT : Objectives: The characteristic of glucose-6-phosphate dehydrogenase (G6PD) deficiency is red blood cell (RBC) destruction in response to oxidative stress. Patients requiring RBC transfusions may simultaneously receive oxidative medications or have concurrent infections, both of which can induce hemolysis in G6PD-deficient RBCs. We intend to investigate the incidence of G6PD deficiency in voluntary blood donors and to evaluate the transfusion risk associated with G6PD deficiency in Guangdong province. Methods: G6PD enzyme was analyzed in 3042 donors and gene mutations were genotyped in G6PD-deficient samples. Results: The G6PD-deficient prevalence of voluntary blood donors was 6.97% (212/3042), 55.19% blood donors with G6PD deficiency donated blood more than twice. Eighty-five cases of G6PD deficiency were genotyped, and the common types of G6PD mutations were c.1376 G > T, c.1388 G > A, c.95 A > G, c.1024 C > T, and c.871 G > A. Conclusions: Due to the high prevalence of G6PD deficiency in Foshan area, we recommended that the screening of G6PD deficiency should be carried out for the regular blood donors to ensure the safety of blood users.